Digital technology use experience and acceptance perceptions as predictors of metaverse attitudes among health professions students in Korea - Jin Young Lee; Kwi Hwa Park; So Jung Yune (Korean Journal of Medical Education, 2026)
Purpose: This study examined differences in digital technology use experience and acceptance perceptions and metaverse attitudes according to major and sex among health professions students. It also determined whether digital technology use experience and acceptance perceptions predicted metaverse attitudes.Methods: An online survey was administered to 1,329 Korean medical, nursing, and dental students. Metaverse attitudes comprised perceived usefulness (PU), perceived ease of use (PEU), and user attitude (UA). Group differences were examined using Welch’s tests, and hierarchical multiple regression identified predictors of PU, PEU, and UA.Results: Nursing students had significantly higher PU and PEU than medical and dental students, whereas dental students had higher UA, indicating stronger negative attitudes and concerns, than the other groups. Digital technology use experience and acceptance perceptions were the strongest positive predictor of PU (β=0.441) and PEU (β=0.447) and negatively predicted UA (β=−0.116).Conclusion: Digital technology use experience and positive acceptance perceptions were closely associated with favorable metaverse attitudes. Metaverse-based educational approaches should be tailored to students’ disciplinary backgrounds and digital technology- related characteristics.